2021
DOI: 10.1177/03057356211027651
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative learning experiences in the university jazz/creative music ensemble: Student perspectives on instructional communication

Abstract: While the ensemble is a ubiquitous learning environment within jazz education, opportunities to learn through engagement in ensemble performances and industry-level recording opportunities are rare classroom environments tertiary jazz music institutions offer. This qualitative study examines jazz performance contexts within an Australian tertiary music course, exploring students’ learning experience spanning three diverse collaborative projects across nine months. Phenomenological analysis explores the instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…Shen et al [ 11 ] applied a text mining method called double-layer concept link analysis, which is a combination of many psychological factors, such as perception, memory, thinking, imagination, and aesthetic experience. In the process of creation, these numerous psychological factors do not appear in an orderly way but are characterized by integrity, organization, and variability, often between various complex psychological factors and technologies, and finally achieve a balance [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Shen et al [ 11 ] applied a text mining method called double-layer concept link analysis, which is a combination of many psychological factors, such as perception, memory, thinking, imagination, and aesthetic experience. In the process of creation, these numerous psychological factors do not appear in an orderly way but are characterized by integrity, organization, and variability, often between various complex psychological factors and technologies, and finally achieve a balance [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…A further search was undertaken after publication of the systematic review, using the same search criteria as reported in Barrett et al (2021), and limiting the year of publication to 2021. Two further studies were identified (Biasutti and Concina, 2021;de Bruin, 2021), making a total of ten papers to be included in our phase two meta-synthesis, reported in this paper.…”
Section: Data Retrievalmentioning
confidence: 99%
“…Approaches to analysis included thematic analysis ( 6), discourse analysis (1), content analysis (2) and interpretive phenomenological analysis (1). Theoretical frameworks included eminence theory of creative practice (Barrett, 2006); social constructivist perspectives (Barrett and Gromko, 2007;Dobson and Littleton, 2016); sociocultural theories of learning and creativity (de Bruin et al, 2020;Biasutti and Concina, 2021;de Bruin, 2021); community of practice (de Bruin, 2016;Virkkula, 2016;Brinck, 2017); and distributed collaboration (Blom, 2012).…”
Section: Data Retrievalmentioning
confidence: 99%
“…For educational work, ensemble activity was noted as having high relevance, especially by using an integration approach to combine art group performance in music, dance, and theatrical elements to create a spectacle (Stakauskaitė, 2021). The collaborative learning experience in musical performance allows experimenting with a variety of genres and styles, including jazz and modern techniques, beyond the regular school classes which "enhance student learning and potentially enculturate richer and more sophisticated musicianship in students and develop their creative abilities" (de Bruin, 2021).…”
Section: Ensemble Practices In Music Educationmentioning
confidence: 99%